1985
DOI: 10.1084/jem.162.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Human natural anti-alpha-galactosyl IgG. II. The specific recognition of alpha (1----3)-linked galactose residues.

Abstract: A natural IgG antibody (anti-Gal) with alpha-galactosyl binding specificity has been found in large amounts (0.5 - 1.0% of serum IgG) in all individuals tested. It has been purified by affinity chromatography on a column of melibiose-Sepharose. In addition to its affinity for normal and pathological senescent human red cells, the antibody readily interacts with rabbit red blood cell (RRBC) glycolipids with alpha-galactosyl terminal residues. Two types (glycosidic linkages of 1----3 vs. 1----4) of rabbit red ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
227
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(235 citation statements)
references
References 23 publications
7
227
0
Order By: Relevance
“…Humans lack a functional ␣1,3-galactosyltransferase (GalT) gene, and therefore do not express Gal␣1,3Gal␀1,4GlcNAc (Gal) carbohydrate residues, and produce abundant natural antibodies (Abs) to the Gal epitope (3). These anti-Gal Abs are a major barrier to xenotransplantation of pig organs into humans, because hyperacute rejection and acute humoral rejection are initiated by their binding to Gal determinants that are ubiquitously present on porcine cells.…”
mentioning
confidence: 99%
“…Humans lack a functional ␣1,3-galactosyltransferase (GalT) gene, and therefore do not express Gal␣1,3Gal␀1,4GlcNAc (Gal) carbohydrate residues, and produce abundant natural antibodies (Abs) to the Gal epitope (3). These anti-Gal Abs are a major barrier to xenotransplantation of pig organs into humans, because hyperacute rejection and acute humoral rejection are initiated by their binding to Gal determinants that are ubiquitously present on porcine cells.…”
mentioning
confidence: 99%
“…30 Anti-Gal interacts specifically with the a-gal epitope (Gala1-3Galb1-4GlcNAc-R), a carbohydrate epitope abundantly produced on glycoproteins and glycolipids of non-primate mammals and New World monkeys by the glycosylation enzyme a1,3galactosyl-transferase (a1,3GT). [31][32][33][34] We and others found that the a-gal epitope is absent, however, in Old World monkeys, apes and humans, because of evolutionary inactivation of the a1,3GT gene in ancestral Old World primates. [34][35][36][37] As an outcome of these evolutionary differences, anti-Gal functions in vivo as a major barrier for xenotransplantation of pig organs in humans, as its binding to a-gal epitopes on pig xenograft cells induces rapid rejection of the graft.…”
mentioning
confidence: 99%
“…These molecules are well characterized for their ability to promote an inflammatory or rejection type response. [189][190][191] ECM scaffold materials containing large amounts of cellular content following decellularization have been demonstrated to promote a more inflammatory, M1 type, response and result in scar tissue deposition rather than constructive remodeling. 73 Although the degree of inflammatory response appears to be linked to the quantity of cellular content, an exact threshold beyond which the constructive remodeling response is affected is unknown.…”
Section: Undesirable Responses To Ecm Scaffold Materialsmentioning
confidence: 99%